Penerapan Green Productivity Untuk Meminimasi Waste Dengan Pendekatan Data Envelopment Analysis Pada Proses Produksi PT. XYZ - Safrillail Ardiyansyah; Rizky Dermawan; Virginia Mandasari (Jurnal Riset Pendidikan Ekonomi, 2026)
Production waste is one of the main challenges in the food processing industry, particularly in the poultry processing sector, which generates large volumes of solid and liquid waste. This issue not only reduces operational efficiency but also poses risks to environmental sustainability. This research aims to apply the Green Productivity concept to minimize waste and improve production efficiency in the nugget processing line at PT XYZ. A descriptive quantitative approach was used with analytical methods including material balance, productivity measurement, waste identification, Environmental Performance Index (EPI), Green Productivity Index (GPI), and Data Envelopment Analysis (DEA). The results indicate that the integration of green productivity significantly enhances production efficiency and reduces waste from oil and flour. The increasing GPI reflects sustainable efficiency, while EPI shows improvements in environmental performance. Furthermore, waste cooking oil was innovatively processed into solid soap as an economical and eco-friendly solution.